Trainee Perspectives of Private Equity's Impact on Ophthalmology - Portney, David S.; Goldstein, Jenna; Berkowitz, Sean T.; Novice, Taylor S.; Patel, Shriji; Law, Janice; Tannen, Bradford (Journal of Academic Ophthalmology, 2023)
Objective The accelerated involvement of private equity (PE) in ophthalmology has many potential implications for the future of the field. The aim of this study was to evaluate trainee perspectives on PE's impact on ophthalmology.Methods An electronic survey was sent to trainees via an online ophthalmology research newsletter. The survey assessed for career goals and perspectives on the involvement of PE and its impact across a variety of attributes.Results A total of 41 United States-based respondents responded to the survey, 68% were medical students and 32% were residents or fellows. Seventy-eight percent of respondents reported they would not consider working for a PE-owned practice. There was a negative perceived impact of PE for physician autonomy, long-term physician income, career advancement, and quality of care. There was a positive perceived impact for the number of physician extenders, more referral sources, financial support, bargaining with insurance companies, starting physician salary, and administrative burden. All respondents agreed (76% strongly agree, 24% somewhat agree) that education about practice options and ownership structures is important to include in residency program education, with preferred modalities of small group discussions and on-site learning.Conclusions Trainees broadly perceive PE to negatively impact the practice of ophthalmology. While there were attributes perceived to be positively impacted by PE, these were not felt to be as important as those which may be negatively affected. New modalities for education about practice ownership options are necessary, and small group discussions and on-site learning may be of the highest yield for trainees.
Keywords: private equity; residency program education; medical students; practice management